Sharia Disclosure Practices: A Comparison of Islamic Banks in Indonesia and Malaysia - Fadila, Nisa Rahma; Muhammad, Rifqi; Subekti, Titin; Nugraheni, Peni; Mohammed, Nor Farizal (Economica: Jurnal Ekonomi Islam, 2021)
The growth of Islamic banking, particularly in Indonesia and Malaysia, has resulted in an increase in assets and disbursement in the two developing countries. This provides an opportunity as well as challenges in implementing good governance to maintain compliance with sharia principles. Involving data from Islamic banks in Indonesia and Malaysia from 2016 to 2018, this study aims to measure the Sharia disclosure level with seven indicators developed from previous research. The results demonstrate that Islamic banks in both countries did not meet the full Sharia disclosure requirement, as evidenced by an index of less than one, namely 0.76 for Islamic banks in Indonesia and 0.57 for Islamic banks in Malaysia. The findings of this study are expected to contribute to the improvement of the management of Islamic banks in both countries, to provide more comprehensive sharia disclosure in their annual report.